2009
DOI: 10.1080/14459790902911653
|View full text |Cite
|
Sign up to set email alerts
|

Impact of survey description, administration format, and exclusionary criteria on population prevalence rates of problem gambling

Abstract: The present study investigated the impact of survey administration format, survey description and gambling behaviour thresholds on obtained population prevalence rates of problem gambling. A total of 3028 adults were surveyed about their gambling behaviour, with half of these surveys administered face-to-face and half over the telephone, and half of the surveys being described as a 'gambling survey' and half as a 'health and recreation' survey. Population prevalence rates of problem gambling using the CPGI wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
167
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(179 citation statements)
references
References 18 publications
11
167
1
Order By: Relevance
“…Although there is some empirical support for the use of self-report for measurement of gambling behaviours (Hodgins & Makarchuk, 2003), self-report is subjective in nature and influenced by emotions, subject to under or overestimates as well as attribution and recall biases (Productivity Commission, 2010). Furthermore, variation in research description, administration of measures and exclusion criteria may result in striking differences in gambling and problem gambling prevalence rates between studies (Williams & Volberg, 2009). Player account data can be analysed in a wide variety of ways and include more than variables measuring gambling behaviour.…”
Section: Advances In Researchmentioning
confidence: 98%
“…Although there is some empirical support for the use of self-report for measurement of gambling behaviours (Hodgins & Makarchuk, 2003), self-report is subjective in nature and influenced by emotions, subject to under or overestimates as well as attribution and recall biases (Productivity Commission, 2010). Furthermore, variation in research description, administration of measures and exclusion criteria may result in striking differences in gambling and problem gambling prevalence rates between studies (Williams & Volberg, 2009). Player account data can be analysed in a wide variety of ways and include more than variables measuring gambling behaviour.…”
Section: Advances In Researchmentioning
confidence: 98%
“…Survey research has generally found that face-to-face interviews are the preferable way to administer gambling research surveys, including measures of problem gambling, as this fosters better rapport and subsequently elicit more candid and honest responses (Williams & Volberg, 2009). Face-to-face surveys also increase recruitment rates of somewhat hard-to-reach populations, including young people (Williams, Volberg, & Stevens, 2012).…”
Section: Trialmentioning
confidence: 98%
“…Notwithstanding a developing picture of the prevalence of problem gambling [21] , the proposed links with mental and physical health suggest over-representation of problems in health-care settings. In this respect, there may be similarities with substance use problems, which predict primary care and emergency usage, and thus burden on health-care systems [22] .…”
mentioning
confidence: 99%